2022
DOI: 10.3390/ani12192600
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Thawing Protocol for Iberian Boar Sperm

Abstract: Thawing protocols have been barely studied, and their modifications may lead to a substantial improvement in post-thawing sperm quality, which could be of great relevance to existing sperm banks, such as those for Iberian pig breeds with varieties in danger of extinction. For that, the study aimed to evaluate different thawing rates and to evaluate modifications in the composition of the thawing extender (basic pH to 8–8.2, incorporation of cyclodextrins loaded with cholesterol [CLC] and the incorporation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Sperm plasma membrane integrity was evaluated using phase contrast microscopy (Nikon Eclipse E400, Tokyo, Japan) coupled with a fluorescence system (Nikon C-SHG1) equipped with a mercury lamp (100 W) and a Nikon filter (510/590 nm), following a previous technique [ 15 ]. An aliquot was diluted with BTS to 30 × 10 6 sperm/mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sperm plasma membrane integrity was evaluated using phase contrast microscopy (Nikon Eclipse E400, Tokyo, Japan) coupled with a fluorescence system (Nikon C-SHG1) equipped with a mercury lamp (100 W) and a Nikon filter (510/590 nm), following a previous technique [ 15 ]. An aliquot was diluted with BTS to 30 × 10 6 sperm/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, samples were fixed in 2% glutaraldehyde, and a minimum of 200 acrosomes were examined per sample. The damage to the acrosome cap was classified by the scoring system previously reported by [ 15 ], and the data are presented in the results as a percentage of spermatozoa with a normal acrosomal ridge (NAR, %)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a fundamental cryobiology point of view, samples that are cooled quickly must be warmed quickly, because samples that are cooled in a quasi equilibrium or nonequilibrium manner will be subject to deleterious recrystallization upon warming, so warming rates must be sufficient to outrun this process [ 174 ]. Semen is no exception [ 175 ]. Hernández found that more-rapid warming resulted in increased motion parameters in boar sperm, with significant interactions among warming rates and glycerol concentrations [ 176 ].…”
Section: Prevention Of Sperm Cryoinjurymentioning
confidence: 99%
“…However, rapid warming rates are more difficult to achieve. Hernández et al, and subsequently Tomás-Almenar and de Mercado, used a 70 °C water bath to achieve this and noted sensitivity on the scale of seconds between successful warming and killing sperm [ 175 , 176 ].…”
Section: Prevention Of Sperm Cryoinjurymentioning
confidence: 99%